MODERN PRINCIPLES OF TRAINING PHYSICAL THERAPISTS - Корчинський, Володимир; Пономаренко, Микола (SWorldJournal, 2025)
The article considers modern aspects of professional training of future specialists in physical rehabilitation in higher educational institutions, which is based on foreign and domestic experience in the conditions of the modern paradigm of higher educati